Blood count, endocrine, immunologic, renal, and hepatic markers in a case-control animal study of induced periodontitis in female rodents - Estarreja, João; Pimenta, Ana Clara; Botelho, João; Vilares, Arminda Maria; Mendes, José João; Rocha, João; Pinto, Rui; Mateus, Vanessa; Machado, Vanessa (Frontiers in Physiology, 2024)
Periodontitis is a non-communicable chronic inflammatory disease with a systemic burden. Animal models of induced periodontitis help elucidate the mechanisms by which periodontal inflammation drives systemic effects. Studying this systemic involvement over longer follow-up periods may provide a strong foundation for future research on the association between diseases and periodontitis, particularly in female rats. Therefore, we aimed to compare blood, endocrine, immunologic, renal, and hepatic markers in a rat model of induced periodontitis in females with their control counterparts. Experimental periodontitis was induced in 20 female Wistar rats by application and maintenance of silk ligatures on the upper molars. The rats were then assessed for macroscopic analysis, complete blood count, biochemical, endocrine, and immunologic markers, at 21, 28, 42, and 56 days. Chronic periodontal inflammation was observed after 42 days of exposure Formatou: Português (Portugal)to the ligatures. Additionally, systemic manifestations have been associated with pronounced reduction of triiodothyronine and thyroxine levels, along with an increase in levels of alkaline phosphatase, gamma-glutamyl transpeptidase and lactate dehydrogenase. The findings of this study may pave the way for future preclinical studies focusing on female-related conditions linked to periodontitis.